Model Identifikasi Pelanggaran Wilayah Udara Berbasis Sistem Pakar Menggunakan Metode Forward Chaining - Kawet, Hetly Brinner Yusak; Heikhmakhtiar, Aulia; Raharjo, Budi (Jurnal Telematika, 2024)
Indonesia is a unitary state with complete and exclusive sovereignty over its airspace, so foreign aircraft must have permission to enter Indonesian airspace. Currently, the identification of foreign aircraft is determined by operators who are vulnerable due to human limitations that can be influenced by human emotions, such as fatigue, depression, and anxiety, which can affect the identification of all aircraft entering Indonesian airspace. Suppose all aircraft to be identified enter Indonesian airspace at the same time with different entry directions and speeds. In that case, it will increase the difficulty for the operator in making decisions on aircraft entering Indonesian airspace as friends or as threats. Using the forward chaining method, the expert system performs reasoning based on the rules for identifying airspace violations. The forward chaining method performs searches using a database of target reports, licensing data, flight plans, and aircraft registration data and performs correlations. This research uses the Java programming language and produces an identification model type of airspace violation that can assist dispatchers in making decisions in mitigation. This research is an innovation that discusses the identification of airspace violations using an expert system.